Pengaruh Lingkungan Kerja Dan Pemberdayaan Pegawai Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Perumda Air Minum Pincuran Gadang Kota Solok - Ricky Ananda; Dori Mitra Candana; Nila Pratiwi (Jurnal Ekonomi dan Bisnis Digital, 2026)
The purpose of this study was to determine the effect of work environment and employee empowerment on employee performance with job satisfaction as an intervening variable on employees of Perumda Air Minum Pancuran Gadang. This study used a data collection method through surveys and distributed questionnaires to 80 respondents. The data analysis technique used was structural equation modeling (SEM) with partial least square (PLS) 3.0. The results of the study showed that there was a positive and significant effect of the work environment on employee performance on Perumda Air Minum Pancuran Gadang employees. There was a positive and significant effect of the work environment on job satisfaction on Perumda Air Minum Pancuran Gadang employees. There was a positive and significant effect of empowerment on employee performance on Perumda Air Minum Pancuran Gadang employees. There was a positive and significant effect of empowerment on job satisfaction on Perumda Air Minum Pancuran Gadang employees. There was a negative and insignificant effect of job satisfaction on employee performance on Perumda Air Minum Pancuran Gadang employees. Job satisfaction was not able to mediate the effect of the work environment on employee performance on Perumda Air Minum Pancuran Gadang employees. Job satisfaction is not able to mediate the influence of empowerment on employee performance at Perumda Air Minum Pancuran Gadang employees.